2016
DOI: 10.1186/s12957-016-0946-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of autophagy-related markers LC3, p62/sequestosome 1, Beclin-1 and ULK1 in colorectal cancer patients with respect to KRAS mutational status

Abstract: BackgroundAutophagy is a cellular pathway that regulates transportation of cytoplasmic macromolecules and organelles to lysosomes for degradation. Autophagy is involved in both tumorigenesis and tumour suppression. Here we investigated the potential prognostic value of the autophagy-related proteins Beclin-1, p62, LC3 and uncoordinated (UNC) 51-like kinase 1 (ULK1) in a cohort of colorectal cancer (CRC) specimens.MethodsIn this study, we analysed the immunoexpression of the autophagy-related proteins p62, LC3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 45 publications
3
96
0
2
Order By: Relevance
“…To clarify if autophagy-associated proteins [14] are detectable in these nuclear inclusions we looked for the presence of the proteins p62/sequestosome1, ubiquitin, LC3B, cathepsin B and cathepsin D by immunohistochemistry. Notably, p62 is also involved in several biological processes [15,16] including NFκB activity, cell proliferation [17,18], apoptosis [19], Keap1-Nrf2 system [20], DNA repair [21,22] and is associated with several cancer types [23][24][25][26][27][28][29][30][31]. In this study we investigated the occurrence of nuclear inclusions in hepatocytes of patients with HCC, characterised the inclusions by means of electron microscopy and immunohistochemistry, and explored if these inclusions have any impact on patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify if autophagy-associated proteins [14] are detectable in these nuclear inclusions we looked for the presence of the proteins p62/sequestosome1, ubiquitin, LC3B, cathepsin B and cathepsin D by immunohistochemistry. Notably, p62 is also involved in several biological processes [15,16] including NFκB activity, cell proliferation [17,18], apoptosis [19], Keap1-Nrf2 system [20], DNA repair [21,22] and is associated with several cancer types [23][24][25][26][27][28][29][30][31]. In this study we investigated the occurrence of nuclear inclusions in hepatocytes of patients with HCC, characterised the inclusions by means of electron microscopy and immunohistochemistry, and explored if these inclusions have any impact on patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe significant association of tumour BECN1, MAP1LC3, and SQSTM1 expression levels with colorectal cancer mortality. Prognostic roles of tumour BECN1, MAP1LC3, and SQSTM1 in colorectal cancer remain controversial, possibly due to differences in study populations, designs, and methods as well as a multifaceted nature of autophagic process [54][55][56][57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a complex multistep process where more than 30 autophagy-related genes have been identified to make up the core machinery [16][17][18][19]. Although BECN1, MAP1LC3, and SQSTM1 have been used widely as immunohistochemistry-based autophagy markers in human FFPE tissues [54][55][56][57][58][59][60][61], a simultaneous multimarker evaluation of other components of the autophagic pathway might further enlighten the interactions between autophagy and microbiota. Finally, we used a qPCR assay for F. nucleatum and Bifidobacterium genus in FFPE tissue specimens; therefore, the detection rates might have been influenced by histopathology procedures and storage conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, western blot results showed increased UBE2Q1 expression in tumor tissues compared to normal cells [20]. The BECN1 gene was identified as the first autophagy marker in human CRC [21]. Zuli Yang et al (2015) studied Beclin-1 levels in CRC cells and found that Beclin-1 expression was higher in CRC cells than in normal cells [22].…”
Section: Discussionmentioning
confidence: 99%